Socialization of Apis Cerana Honey Bee Cultivation to Improve the Economy of the Kanagarian Community Malai Iii Koto Sungai Geringging Padang Pariaman: Sosialisa Budidaya Lebah Madu Apis Cerana Untuk Meningkatkan Perekonomian Masyarakat Kanagarian Malai Iii Koto Sungai Geringging Padang Pariaman - Jasmi; Henny Herwina; Gustina Indriati; Friska Eka Fitria; Yenni Herlina; Weni Murdina (Journal of Community Service and Application of Science, 2022)
The Apis cerana honey bee is a natural resource that may be developed for beekeeping in Nagari Malai III Koto, Sungai Geringging District, Padang Pariaman, West Sumatra. The potential of these bees is developed, either as a single business as a honey producer or integrated with various types of plants. The main supporting factors for Apis cerana beekeeping are the presence of bee colonies found in people's gardens and the availability of abundant food throughout the year produced by plantation, fruit, and forestry crops. In addition, there are human resources from academics and professionals scattered in various regions. The prospect of Apis cerana honey beekeeping needs to be socialized to the farming community through counseling so that the potential of Apis cerana bees can be maximized. The socialization was carried out by means of counseling and demonstration methods to farmers and their families as the target audience and accompanied by the government of Nagari Malai III Koto. The results obtained that socialization carried out by extension and demonstration methods could disseminate information, increase the knowledge and interest of farmers and farming families about Apis cerana honey beekeeping